THE ASSESSMENT OF THE IMPACT OF VITAMIN D ON THE INTENSITY OF LOWER URINARY TRACT SYMPTOMS AND THE QUALITY OF LIFE OF PERSONS WITH BENIGN PROSTATIC HYPERPLASIA - Pelicic, Damir; Kovacevic, Rada (HEALTH CARE, 2023)
Introduction/Aaim: Older men with benign prostatic hyperplasia (BPH) are more likely to have a poor quality of life. The aim of this study was to examine the influence of serum vitamin D on the intensity of lower urinary tract symptoms and the quality of life of persons with benign prostatic hyperplasia. Methods: The study was conducted as a cross-sectional study. The study included 117 persons with benign prostatic hyperplasia (BPH) treated at the Clinical Center of Montenegro in Podgorica from May 10th, 2022 to August 15th, 2022. Data were collected with the help of the general questionnaire from electronic medical records, as well as with the International Prostate Symptom Score (IPSS) questionnaire. Spearman’s correlation coefficient was used for the statistical analysis of data. Results: The average age of participants was 62.97±11,57. The average value of the intensity of symptoms in patients with BPH according to the IPSS questionnaire was 8.54. Of the 117 participants with BPH, 57 (48.7%) had moderate symptoms, 56 (47.9%) mild, and 4 (3.4%) severe. A significant negative correlation (r=-0.316; p=0.010) was obtained between vitamin D levels and average values of symptoms according to the IPSS questionnaire. Also, a significant negative correlation was obtained between serum vitamin D values and all individually assessed values of BPH symptoms according to the IPSS questionnaire (sensation of incomplete emptying of the bladder during urination – p=0.040; repeated urination within two hours from the previous urination – p<0.001; intermittent urination – p=0.005; inability to postpone urination – p=0.036; a thin and weak urinary stream – p=0.001; straining to begin urinating with the sensation of the need to urinate – p=0.046 and nocturia – p=0.011). Based on the serum level of vitamin D, the participants had optimal levels of vitamin D in 52.1% of cases, insufficient levels in 29.1% of cases and deficit in 18,8%. An inverse relationship between the average values of serum vitamin D and quality of life according to ISPP questionnaire was observed, but this relationship was not significant (r =-0.365; p=0.160). Conclusion: The results of the study show that higher levels of vitamin D lead to the significant reduction in urological symptoms in patients with BPH, which points to the need to prevent vitamin D deficiency. Further research in this field is necessary aimed at making more detailed recommendations.